The Effectiveness of Nutritional Interventions on Hypertension Control: A Meta-Analysis - Farras, Reyhan Muhammad (Journal La Medihealtico, 2024)
This study aims to evaluate the effectiveness of nutritional interventions in addressing hypertension, considering aspects such as food consumption, dietary patterns, and other nutritional interventions. Through meta-analysis, the research seeks to consolidate findings from various previous studies to provide a stronger conclusion regarding the effectiveness of nutritional interventions on hypertension and to establish a foundation for the development of more effective nutritional intervention programs for the prevention and control of hypertension. The research methodology employs a meta-analysis approach and literature research to evaluate relevant journal articles on the topics of "Hypertension," "Blood Pressure," and "Nutrition." Article selection criteria include publication years from 2015 to 2023, written in Indonesian or English, and document types "article research" and "review literature," resulting in a final selection of 10 articles for the meta-analysis study. The study findings indicate that nutritional interventions, such as reducing salt intake and adopting the DASH diet, are effective in lowering blood pressure, especially in individuals at high risk of hypertension. Dietary fiber supplements and early-life interventions also prove to significantly benefit blood pressure management. Holistically, emphasis on healthy eating patterns, active lifestyles, and the use of technologies like mHealth can help address hypertension issues among at-risk populations.